2011
DOI: 10.1038/sc.2011.6
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic myelopathies and traumatic spinal cord lesions: an Italian comparison of functional and neurological outcomes

Abstract: Background: Although neoplastic spinal cord injuries (NSCIs) constitute B25% of all non-traumatic spinal cord lesions, patients with such pathologies are seldom, if ever, admitted to specialized centers; further, their rehabilitation typically is short because of the perception that rehabilitation prolongs hospital stays unnecessarily and is reserved only for patients with very good prognoses. Study design: This study is a retrospective analysis. Objective: The objective of this study is to evaluate the neurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
3
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 28 publications
(42 reference statements)
6
21
3
4
Order By: Relevance
“…A number of reports compared people with SCDys due to tumor to those with traumatic SCI and found that the tumor group had a shorter length of stay in SRU, comparable improvement in functional abilities and similar rates of discharge back into the community. 15,27 A number of publications reported on the functional outcomes of people with SCDys due to tumor, with the consistent finding that they had a significant functional improvement between admission and discharge. 5,15,16,26 Compared to people with traumatic SCI, however, their functional improvement was less.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of reports compared people with SCDys due to tumor to those with traumatic SCI and found that the tumor group had a shorter length of stay in SRU, comparable improvement in functional abilities and similar rates of discharge back into the community. 15,27 A number of publications reported on the functional outcomes of people with SCDys due to tumor, with the consistent finding that they had a significant functional improvement between admission and discharge. 5,15,16,26 Compared to people with traumatic SCI, however, their functional improvement was less.…”
Section: Literature Reviewmentioning
confidence: 99%
“…15,27 A number of publications reported on the functional outcomes of people with SCDys due to tumor, with the consistent finding that they had a significant functional improvement between admission and discharge. 5,15,16,26 Compared to people with traumatic SCI, however, their functional improvement was less. 15,27 In comparison with other causes of SCDys, people with tumor have a trend towards lower functioning on admission and at discharge, and possibly lower overall change in function when compared with the other causes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Previous reports on their rehabilitation outcomes have been published. [7][8][9][10] These patients can have a relatively short survival, 11,12 and have a peak age at the time of diagnosis of between 50 and 70 years. 13 With the ageing population and improvements in early cancer diagnosis and treatment leading to increased survival, the number of patients with SCI due to tumour with the potential to benefit from rehabilitation is increasing.…”
Section: Introductionmentioning
confidence: 99%